Leadership Discipline and Motivation Patterns in Employee Performance: Disiplin Kepemimpinan dan Pola Motivasi dalam Kinerja Karyawan - Zidni, Moh. Luthfi; Firdaus, Vera (Indonesian Journal of Law and Economics Review, 2025)
General Background Employee performance remains a central concern in organizational management amid increasing competitive pressure. Specific Background Leadership style, work discipline, and employee motivation are frequently discussed as internal managerial factors associated with performance outcomes. Knowledge Gap Previous studies often examine these variables separately, leaving limited empirical evidence on their combined examination within a single organizational setting. Aims This study aims to examine leadership, work discipline, and motivation in relation to employee performance within the observed organization. Results The findings indicate that leadership, work discipline, and motivation demonstrate statistically significant relationships with employee performance based on quantitative analysis using survey data. Novelty This research provides integrated empirical evidence by simultaneously analyzing leadership, discipline, and motivation within one analytical framework at the organizational level. Implications The results offer managerial insights for organizational leaders in structuring leadership practices, reinforcing discipline, and fostering employee motivation to support performance-oriented management. Keywords: Leadership, Work Discipline, Motivation, Employee Performance, Human Resource Management Key Findings Highlights: Employee performance is closely associated with leadership, discipline, and motivational conditions. Work discipline demonstrates a consistent role within the examined organizational setting. Integrated managerial factors provide a clearer understanding of performance dynamics.